1975
DOI: 10.2307/3279217
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Cysticerci of Taenia taeniaeformis after Mebendazole Treatment

Abstract: The progressive micromorphological changes in Taenia taeniaeformis cysticerci, induced by a single parenteral treatment of the infected mice with mebendazole, are described. The time-related alterations concerned the tegument and tegumental cells and were successively: disappearance of microtubules, accumulation of secretory substances in the Golgi areas, decrease in number to complete loss of microtriches, "ballooning" of all tegumental cells with subsequent burst, vacuolization and degeneration of the tegume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…It is also similar to that observed in F. hepatica and other flatworm parasites following exposure to mebendazole, another benzimidazole compound (Borgers et al 1975;Verheyen et al 1982). This might suggest that, while TCBZ may not bind to the b-tubulin molecule at the same binding site as other benzimidazoles (Lacey 1988;Nare et al 1996;Fairweather and Boray 1999), its effects may be caused by disruption of the same target, perhaps via binding to an alternative site on the b-tubulin molecule.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is also similar to that observed in F. hepatica and other flatworm parasites following exposure to mebendazole, another benzimidazole compound (Borgers et al 1975;Verheyen et al 1982). This might suggest that, while TCBZ may not bind to the b-tubulin molecule at the same binding site as other benzimidazoles (Lacey 1988;Nare et al 1996;Fairweather and Boray 1999), its effects may be caused by disruption of the same target, perhaps via binding to an alternative site on the b-tubulin molecule.…”
Section: Discussionsupporting
confidence: 75%
“…This form of disruption has also been observed in other flatworm parasites (Borgers et al 1975;Bricker et al 1983) and is believed to be a calcium-dependent process (Bricker et al 1983;Xiao et al 1984). In F. hepatica, it has been suggested that the blebbing occurs as a result of increased efforts on the part of the parasite to shed and replace outer tegumental membrane damaged by drug action (Stitt and Fairweather 1993).…”
Section: Discussionmentioning
confidence: 85%
“…Similar changes have been seen in anthelmintic studies on other trematode and cestode parasites (Borgers et al 1975;Becker et al 1981;Bricker et al1983). Blebbing and swelling of the tegument are believed to represent a stress reaction, the parasite attempting to replace damaged tegument (Bricker et al 1983;Stitt and Fairweather 1993).…”
Section: Discussionmentioning
confidence: 55%
“…Among other benzimidazole dérivâtes, mebendazole is a broad spectrum anthelmintic compoud acting against nematode and cestode infections in mammals (Borgers et al 1975). In gênerai, mebendazole acts as a potent inhibitor of glucose uptake.…”
Section: Benzimidazole Dérivâtesmentioning
confidence: 99%